59‐1: Invited Paper: Modeling and Suppressing of Color Breakup. Issue 1 (May 2016) - Zhang, Yuning; Wang, Jian; Wang, Lili; Tu, Yan; Li, Xiaohua
Abstract : Field‐sequential color displays are used as an alternative to the standard displays where energy consumption can be reduced or peak luminance can be increased. Its spatial resolution is potentially three times higher compared to a conventional color filter LCD. The concept of field sequential color displays shows the problem of color breakup artifact. This paper reviews the cause and the factors for the perception of color breakup, discusses the approaches for the reduction of color breakup. It is suggested that, with field‐sequential color algorithm, 180Hz or 240Hz LC panel could have potential market in the high luminance and high resolution display applications.